1989
DOI: 10.1203/00006450-198908000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Direct Long-Term Effects of L-Asparaginase on Rat and Human Pancreatic Islets

Abstract: ABSTRACT. L-Asparaginase, an effective agent in the treatment of acute lymphoblastic leukemia, may induce a diabetic state. The pathogenesis of the diabetogenic effect was studied in cultured pancreatic islets. Mean serum concentrations in three children with acute lymphoblastic leukemia were 2.4 U/mL (range 1.4-4.5) before and 31.5 U/mL (range 18.6-51.8) immediately after an intravenous injection of 1000 U/kg L-asparaginase. Glucose-induced insulin release from pancreatic islets of rat and man was measured af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The pancreatic b-cells are sensitive to chemotherapeutic drugs, in particular l-Ase, used in patients with ALL during remission-induction treatment (4). l-Ase seems to exert a direct toxic effect with structural and functional alterations of the b-cells, leading to a reduced insulin production (20). One patient in our series developed acute hyperglycemia and cerebral edema after the first dose of l-Ase.…”
Section: Discussionmentioning
confidence: 70%
“…The pancreatic b-cells are sensitive to chemotherapeutic drugs, in particular l-Ase, used in patients with ALL during remission-induction treatment (4). l-Ase seems to exert a direct toxic effect with structural and functional alterations of the b-cells, leading to a reduced insulin production (20). One patient in our series developed acute hyperglycemia and cerebral edema after the first dose of l-Ase.…”
Section: Discussionmentioning
confidence: 70%
“…The hyperglycemic effect of asparaginase is also dose‐dependent and results from a decrease in insulin secretion from pancreatic islet cells 1, 2. In vitro and in vivo studies have demonstrated that the combination of steroids and asparaginase results in a greater degree of hyperglycemia than either medication alone 15, 16.…”
Section: Discussionmentioning
confidence: 99%
“…(15, 22) At higher concentrations in vitro , asparaginase has been demonstrated to cause irreversible alteration of asparagine in the cells and/or islet cell death. (25, 26) Based on these mechanisms, prolonged abnormalities of glucose metabolism, manifested as hyperglycemia and hypoinsulinemia would be expected in patients who have received asparaginase therapy. Mohn et al previously studied ALL survivors and found decreased insulin secretion in glucose tolerance testing.…”
Section: Discussionmentioning
confidence: 99%